2020
DOI: 10.1038/s41467-019-13745-7
|View full text |Cite
|
Sign up to set email alerts
|

Arginine π-stacking drives binding to fibrils of the Alzheimer protein Tau

Abstract: Aggregation of the Tau protein into fibrils defines progression of neurodegenerative diseases, including Alzheimer's Disease. The molecular basis for potentially toxic reactions of Tau aggregates is poorly understood. Here we show that π-stacking by Arginine side-chains drives protein binding to Tau fibrils. We mapped an aggregation-dependent interaction pattern of Tau. Fibrils recruit specifically aberrant interactors characterised by intrinsically disordered regions of atypical sequence features. Arginine re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 73 publications
(99 reference statements)
5
38
0
Order By: Relevance
“…Consequently, it is perhaps not surprising that fibrils with different structures may induce different effects in vivo. Ferrari et al (2020), for example, used a pull-down approach with FLAG-tagged Tau to show that different aggregation stages (monomer, oligomer, fibril) have altered reactivity with its cellular environment due to large conformational changes that occur when this natively unfolded protein self-assembles into a β-sheet rich fibrillary protein state. Given that the "fuzzy coat" of disordered peptide regions that flank the cores of amyloid fibrils can vary between fibril polymorphs (Gallardo et al, 2020b), the effect of these dynamic regions on the function, toxicity and further amplification of the fibrils themselves may also vary, perhaps rationalizing the epigenetic difference in disease development in individuals expressing the same aggregation-prone proteins.…”
Section: Regions Flanking the Structured Core Of Amyloid Fibrils: Thementioning
confidence: 99%
“…Consequently, it is perhaps not surprising that fibrils with different structures may induce different effects in vivo. Ferrari et al (2020), for example, used a pull-down approach with FLAG-tagged Tau to show that different aggregation stages (monomer, oligomer, fibril) have altered reactivity with its cellular environment due to large conformational changes that occur when this natively unfolded protein self-assembles into a β-sheet rich fibrillary protein state. Given that the "fuzzy coat" of disordered peptide regions that flank the cores of amyloid fibrils can vary between fibril polymorphs (Gallardo et al, 2020b), the effect of these dynamic regions on the function, toxicity and further amplification of the fibrils themselves may also vary, perhaps rationalizing the epigenetic difference in disease development in individuals expressing the same aggregation-prone proteins.…”
Section: Regions Flanking the Structured Core Of Amyloid Fibrils: Thementioning
confidence: 99%
“…Moreover, BRCA1, a DNA nuclear protein, has been found to mis-localize and deposit with tau in different tauopathies, possibly causing loss of function and reducing DNA repair [56]. Furthermore, incubating different aggregated species of tau with rat brain lysate revealed a distinct interaction pattern compared to monomeric tau [57], suggesting that aggregate-specific interactions occur. Interestingly, interactions changed during the course of aggregation.…”
Section: Heterogeneity Of Amyloid Depositsmentioning
confidence: 99%
“…Early interactions contained proteins connected to Coat Protein I components, which in late stage aggregates were decreased in abundance [57]. In contrast, during these later stages of aggregation, proteins connected to RNA, phosphorylation and microtubules were able to interact highly with tau fibrils [57]. Co-immunoprecipitation of tau from microsomes isolated from AD and control brains showed that 42.9% of the proteins identified were only found in AD brains, with proteins involved in RNA translation having higher abundances [58].…”
Section: Heterogeneity Of Amyloid Depositsmentioning
confidence: 99%
“…Polymerase δ-interacting protein 2 (PolDIP2, also known as PDIP38) has recently been identified as a specific binding partner of Tau monomers, but not Tau oligomers or fibrils [6]. PolDIP2 is a multi-functional protein originally described as a binding partner of the nuclear DNA polymerase Pol δ and proliferating cell nuclear antigen [7,8], but previous reports have suggested that PolDIP2 has also a regulatory role in cellular Tau aggregation [6,9]. The mechanism by which PolDIP2 regulates Tau aggregation remains to be addressed.…”
Section: Introductionmentioning
confidence: 99%